Purpose, meaning, and passion - Sprinkle, Ann; Price, Justin (HBR emotional intelligence series., 2022)
Find your purpose at work. In an ideal world, our work lives would be completely fulfilling and intrinsically motivating. But what if you're stuck in a job and your heart isn't in it anymore? Or what if your company's mission seems unrelated to the work you do day in and day out? This book showcases the power of passion-and how you and your team can find it at work. This volume includes the work of: Morten T. Hansen, Teresa M. Amabile, Scott A. Snook, and Nick Craig. This collection of articles includes "Finding Meaning at Work, Even When Your Job Is Dull," by Morten Hansen and Dacher Keltner; "What to Do When Your Heart Isn't in Your Work Anymore," by Andy Molinsky; "You Don't Find Your Purpose-You Build It," by John Coleman; "How to Find Meaning in a Job That Isn't Your True Calling," by Emily Esfahani Smith; "You're Never Done Finding Purpose at Work," by Dan Pontefract; "From Purpose to Impact," by Nick Craig and Scott A. Snook; "Five Questions to Help Your Employees Find Their Inner Purpose," by Kristi Hedges; "How to Make Work More Meaningful for Your Team," by Lewis Garrad and Tomas Chamorro-Premuzic; "The Power of Small Wins," by Teresa M. Amabile and Steven J. Kramer; and "The Founder of TOMS on Reimagining the Company's Mission," by Blake Mycoskie